Performance evaluation of steel reduced flange plate moment connections. - Chou, Chung-Che
This study details a new moment connection that overcomes difficulties in achieving field-weld quality and eliminates steel beam buckling encountered in steel moment connections. This study presents cyclic test and finite element analysis results of full-scale subassemblies using steel reduced flange plates (RFPs) to connect steel beam flanges and the column without any other direct connection. Since the RFP connection is designed as strong column-strong beam-weak RFPs, the RFP functions as a structural fuse that eliminates weld fractures and beam buckling. Test and analytical results show that (1) the connections transferred the entire beam flexural strength to the column and reached an interstorey drift of 4% with minor strength degradation, (2) failure of the connections was owing to buckling or fracturing of the RFP and not of the beam, and (3) the RFP connection subassembly, modelled using the nonlinear finite element computer program ABAQUS, exhibited hysteretic behaviour similar to that of the flange plate (FP) moment connection subassembly. The inelastic buckling force of the RFP was also evaluated by nonlinear regression analyses performed on a nonlinear model that relates buckling force to RFP geometries.
Keywords: Reduced flange plate moment connection; Cyclic test; Finite element analysis; Nonlinear regression analysis; Buckling